Cluster analysis as a tool for evaluating the exploration potential of Known Geothermal Resource Areas. (March 2018) - Lindsey, Cary R.; Neupane, Ghanashym; Spycher, Nicolas; Fairley, Jerry P.; Dobson, Patrick; Wood, Thomas; McLing, Travis; Conrad, Mark
Highlights: We present a new method for evaluating site geothermal exploration potential. We use PCA and cluster analysis to evaluate literature data from multiple sites. Candidate areas are compared to high and low geothermal potential control sites. The method is robust to data of variable quality, resolution, and granularity. Abstract: Although many Known Geothermal Resource Areas in Oregon and Idaho were identified during the 1970s and 1980s, few were subsequently developed commercially. Because of advances in power plant design and energy conversion efficiency since the 1980s, some previously identified KGRAs may now be economically viable prospects. Unfortunately, available characterization data vary widely in accuracy, precision, and granularity, making assessments problematic. Here we suggest a procedure for comparing test areas against proven resources using Principal Component Analysis and cluster identification. The result is a low-cost tool for evaluating potential exploration targets using uncertain or incomplete data.